The Elite Deliberative Democratic Model in The Public Policy Formulation for Madrasah Diniyyah (Islamic Non Formal School) Development in East Java, Indonesia - Ismail Ismail; Moh Wardi (FITK UIN Walisongo, 2019)
This research intend to discuss about public policy from East Java province government to improve the quality of Islamic religious education. The results of this study were: (1) East Java Provincial Government used policy formulation model in the name